Penetapan Kadar Natrium Benzoat Pada Cabai Giling Halus (Capsicum annuum Linn.) Secara Spektrofotometri Uv-Vis - Henni Rosaini; Zulharmita Zulharmita; Susi Yuliana (STIFARM Padang, 2016)
The reseacrh about identification and assay of sodium benzoate content in fine milled chilli taken from three locations which were Pasar Ibuh Payakumbuh, Pasar Bawah Bukittinggi and Pasar Raya Padang had been done, two samples were taken from each location. It was found that three samples gave positive indication by esterification reaction to the presence of sodium benzoate in samples. Assay of sodium benzoate in samples after extraction with ether as a solvent were carried out using ultraviolet spectrophotometer. The benzoic acid content of the positive samples were found to be in the range of 0.811-0.976 g/kg. This amount of benzoic acid content fine milled chilli samples were below the maximum amount allowedaccording to the rule stated by to National Agency of Drug and Food Control Republic of Indonesia No. 36/2013 which was 1 g/kg, so it was safe to consume.